Diversity and functional profile of gut symbiotic bacteria between Lysinibacillus sphaericus C3-41 susceptible and resistant Culex quinquefasciatus Say as revealed by 16S rRNA gene high-throughput sequencing - Zhang, Xiaolei; Meng, Haoran; Hu, Xiaomin; Yuan, Zhiming (Frontiers in Microbiology, 2022)
Previous studies have demonstrated that gut symbiotic bacteria were involved in the resistance development against insecticides in insects, but the relationship between the gut symbiotic bacteria and resistance to Lysinibacillus sphaericus C3-41 in Culex pipiens quinquefasciatus remains unclear. In this study, the abundance and diversity of gut symbiont of Cx. quinquefasciatus were analyzed by high-throughput sequencing data of 16S rRNA and the difference of the gut symbiotic bacterial communities between the two mosquito colonies was observed. The NMDS (Non-Metric Multi-Dimensional Scaling) and unweighted unifrac PCoA analysises revealed that gut symbiotic bacterial communities from resistant strain differed significantly from the bacterial communities in gut of susceptible strain，suggesting that bacterial insecticide could alter bacterial composition and finally resulting the resistance development. The bacteria Rhodocyclaceae bacterium could help their host fight bacterial insecticide and lead to resistance development. These results will be helpful for further research into the mechanisms of gut symbionts involved in resistance against L. sphaericus C3-41 in Cx. quinquefasciatus.